Evaluation of the effectiveness of Ampicillin and Lactobacillus casei rhamnosus treatment in cases of preterm premature rupture of membranes remote from term - Kavak, Salih Burcin; Kavak, Ebru Celik; Senocak, Ahmet; Haliscelik, Mesut Ali; Cim, Bunyamin; Sapmaz, Ekrem (Via Medica, 2022)
Objectives: Preterm premature rupture of membranes (PPROM) remote from term is an important obstetric cause of maternal and fetal adverse outcomes. The aim of our study is to examine the efficacy of ampicillin and Lactobacillus casei rhamnosus treatment in cases of PPROM remote from term.Material and methods: The study was carried out by examining the results of cases who were given Ampicillin and Lactobacillus casei rhamnosus treatment. The patients were divided into two groups. Group 1 who didn't develop clinical chorioamnionitis and Group 2 who developed clinical chorioamnionitis. Obstetric characteristics, neonatal outcomes, adverse events were recorded.Results: A total of 46 pregnant women, 40 in Group 1 and six in Group 2, were included in the study. The frequency of clinical chorioamnionitis developing during the treatment was found to be 13.0%. Mean gestational age at diagnosis was 28.43 +/- 2.38 and 28.17 +/- 1.33 for Groups 1 and Group 2, respectively. Mean gestational age at the time of delivery was 32.38 +/- 2.07 31.33 +/- 1.63 for Group 1 and Group 2, respectively. The mean latency period for Group 1 and Group 2 was 27.45 +/- 1.71 days, 23.66 +/- 4.53, respectively. Sepsis developed in six newborns (15%) in Group 1, while it developed in three newborns (50%) in Group 2. While 90% of the babies in Group 1 were discharged from the hospital, this rate was 66.7% in Group 2.Conclusions: Ampicillin + Lactobacillus casei rhamnosus is an effective treatment method in PPROM cases and positively affects perinatal outcomes.
Keywords: preterm premature rupture of membranes; ampicillin; L; casei rhamnosus; clinical chorioamnionitis